Auto/Biography and the Construction of Identity and Community in the Middle East - Rachel Christina (International Institute of Islamic Thought, 2002)
This collection of reflective essays and research articles argues for the greater use of auto/biographies, both as data sources and as representational texts, in examining individual and communal identity negotiations in the Middle East. It reflects the theoretical and topical shifts toward the local, regional, and particular that characterize poststructuralist and postmodernist social science research. It also resonates to the increased concern about representing marginalized populations in historical, sociological, and anthropological literature. Positing that "biography lies at the intersection of the personal and the political and of public and private history," Fay calls for a more flexible, interpretive, and micro-focused understanding of the relationship between individuals and their contexts. She also champions auto/biography as both a means of entry into private lives and a lens through which to view those lives as part of a broader sociohistorical milieu. The various authors assert that such a use of biography is consistent with traditional Arab and Islamic forms of representation - a claim that recenters the Middle East within the social sciences as a key site of know I ...